2006
DOI: 10.1161/circulationaha.105.000240
|View full text |Cite
|
Sign up to set email alerts
|

Increased Collagen Deposition and Elevated Expression of Connective Tissue Growth Factor in Human Thoracic Aortic Dissection

Abstract: Background-Thoracic aortic dissection (TAD) is characterized by dysregulated extracellular matrix. Little is known about the alterations of collagen and stimulators of collagen synthesis, eg, connective tissue growth factor (CTGF), in patients with TAD. In this study, we examined their roles in TAD. Methods and Results-Surgical specimens of the aortic wall of TAD patients (nϭ10) and controls (nϭ10) were tested for collagen types I and III and CTGF expression. When compared with controls, protein levels of type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 25 publications
9
101
1
3
Order By: Relevance
“…Adventitial remodeling and thickening is characterised by an increase in Extracellur Matrix (ECM) protein deposition. The previous study revealed the adventitia to be the main site of collagen deposition in the aortic wall [29]. CTGF is known to mediate aortic adventitial fibroblast collagen synthesis stimulated by Angiotensin-II (Ang II) [30] and it is conceivable that, in our study, the hypertrophy and remodeling that we observed in aorta root is directly the result of collagen accumulation in adventitia and the increase in renin synthesis in the aorta root.…”
Section: Discussionsupporting
confidence: 50%
“…Adventitial remodeling and thickening is characterised by an increase in Extracellur Matrix (ECM) protein deposition. The previous study revealed the adventitia to be the main site of collagen deposition in the aortic wall [29]. CTGF is known to mediate aortic adventitial fibroblast collagen synthesis stimulated by Angiotensin-II (Ang II) [30] and it is conceivable that, in our study, the hypertrophy and remodeling that we observed in aorta root is directly the result of collagen accumulation in adventitia and the increase in renin synthesis in the aorta root.…”
Section: Discussionsupporting
confidence: 50%
“…We also showed that inhibition of β-catenin signaling downregulates CTGF-induced collagen 1a1 expression. Collagen 1a1 is one of the most important ECM that is associated with progressive pulmonary and vascular fibrosis (37). Many studies have demonstrated that CTGF upregulates collagen 1a1 expression in many types of cells including lung fibroblasts and vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of CTGF has been found in atherosclerotic carotid arteries and in the aortic wall from patient with thoracic aortic dissection [8,44] . Based on the result of this study, together with evidence from clinical specimens, it might suggest that CTGF is one of the mediators in the progression of atherosclerosis [44] . There are many new and emerging antithrombotic agents including PAR-1 antagonists, thrombin inhibitors, etc [45,46] .…”
Section: Discussionmentioning
confidence: 99%